Bahasa Inggris: Bahasa Inggris - Andika Aulia; Aghnia Dian lestari (CV. AFDIFAL MAJU BERKAH, 2026)
Authoritarian parenting, characterized by parental dominance and limited two-way communication, has the potential to restrict children’s freedom of expression within family relationships. This study aims to analyze the representation of the suppression of children’s expression within an authoritarian parenting style in the film Dead Poets Society. This research employs a qualitative approach using Roland Barthes’s semiotic analysis to examine denotative, connotative, and mythical meanings through visual signs and dialogue. Data were collected through film observation, in depth interviews, and documentation. The findings reveal that the father child relationship is represented hierarchically through one way communication, parental dominance in decision-making, and nonverbal expressions indicating emotional pressure. These representations construct a myth that parental authority is absolute and must be obeyed. Therefore, the film portrays authoritarian parenting as a symbolic mechanism that contributes to the suppression of children’s expression within family relationships.